1999
DOI: 10.1086/316675
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fasting on Blood and Plasma Composition of Herring Gulls (Larus argentatus)

Abstract: Populations of scavenging seabird species in the North Sea may fluctuate with an artificial food source: the availability of fishery waste. To document this impact, it is necessary to assess the birds' nutritional status during periods with decreased fishing activity. Reference data for this purpose was collected from 22 herring gulls investigated during laboratory fasting. After 6 d of food deprivation and body mass losses exceeding 15%, the first birds entered starvation phase 3. Comparatively, this is a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 58 publications
2
93
5
Order By: Relevance
“…Dabbert et al (1997) found that blood triglyceride levels predicted (rϭ0.57; Pϭ0.007) total body fat in mallard drakes. Measurements of plasma total protein, albumin, uric acid, urea, free fatty acids, cholesterol, ␤-hydroxybutyrate, and thyroid hormones may also give reliable information about nutritional status of birds (Totzke et al, 1999;Gannes, 2001;Hollmé n et al, 2001;Alonso-Alvarez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dabbert et al (1997) found that blood triglyceride levels predicted (rϭ0.57; Pϭ0.007) total body fat in mallard drakes. Measurements of plasma total protein, albumin, uric acid, urea, free fatty acids, cholesterol, ␤-hydroxybutyrate, and thyroid hormones may also give reliable information about nutritional status of birds (Totzke et al, 1999;Gannes, 2001;Hollmé n et al, 2001;Alonso-Alvarez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Ronald and George (1988) found WBC counts to peak in fall in captive Canada geese. Totzke et al (1999) experimentally starved herring gulls and found no changes in total WBC count but found a shift in WBC composition from lymphocytes to heterophils, with monocytes and basophils remaining constant and eosinophils being undetectable.…”
Section: Discussionmentioning
confidence: 94%
“…The seasonal cycles in mass, moult, and plumage of the captive ruffs and red knots appeared to be unaffected; there were no indications that bleeding had negative effects on either hematocrit or percent WBCs. But, as shown by the apparently undernourished red knots and experimentally fasted herring gulls (Totzke et al 1999), birds may be physiologically less resistant to bleeding if their nutritional status is somehow compromised. This should be taken into account in studies on birds living in conditions that are potentially stressful.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the rapid movement of extracellular fluid into the capillaries is so rapid and strong that it can overshoot the pre-hemorrhage blood volume within a few minutes (Takei and Hatakeyama 1987). This replacement fluid results in a diluting effect that is manifest by a reduction in hematocrit values (Djojosugito et al 1968, Kovách and Balint 1969, Ploucha et al 1981, Gildersleeve et al 1985, Dressen et al 1999, Totzke et al 1999, Piersma et al 2000.…”
Section: Discussionmentioning
confidence: 99%